Analisis Produk Banane Shampoo - Diana Vimalakirti Chow; Hardi Suandri; Herman Herman; Ricky Ricky (Journal Of Business, Finance, and Economics (JBFE), 2022)
Banana is an agricultural product that is highly developed in Indonesia. Bananas can be easy to grow and reproduce. Rapid and continuous development brings satisfactory results. Bananas need a place to grow in a hot and humid tropical climate to grow and develop. Banana plant is a multifunctional and multipurpose plant. Apart from fruits, other parts can be used. Banana weevil can be processed into chips. Kepok banana peel stems can also be used as a liquid ingredient to remove dirt on the surface of the scalp or/usually as a shampoo. Kepok banana fruit is one type of banana fruit that contains relatively high nutrients. Because kepok bananas contain chromium which has benefits for carbohydrate and lipid metabolism.